2019
DOI: 10.1038/s41598-019-49091-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative function of follicular fluid HDL and outcomes of modified natural cycle-IVF

Abstract: High density lipoproteins (HDL) are the main cholesterol carriers in follicular fluid (FF), the natural environment of oocyte development. Additionally, HDL have critical biological functions such as anti-oxidative capacity, which have not been studied in reproduction. Therefore, this study aimed to investigate whether the anti-oxidative function of FF-HDL is associated with fertility outcomes. From 253 women undergoing modified natural cycle (MNC)- IVF at a single academic centre FF and plasma were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…However, the current study found that HI and IR were not associated with clinical pregnancy rate, live birth rate, and miscarriage rate in women without PCOS. Although some studies reported that metabolic and ovarian stimulation outcomes might negatively affect reproductive outcomes (31)(32)(33)(34)(35)(36)(37)(38), the current study did not recommend treating HI and IR for non-PCOS women undergoing assisted reproduction. However, the women in our study were relatively young, lean, and had a lower prevalence of HI and IR.…”
Section: Discussionmentioning
confidence: 66%
“…However, the current study found that HI and IR were not associated with clinical pregnancy rate, live birth rate, and miscarriage rate in women without PCOS. Although some studies reported that metabolic and ovarian stimulation outcomes might negatively affect reproductive outcomes (31)(32)(33)(34)(35)(36)(37)(38), the current study did not recommend treating HI and IR for non-PCOS women undergoing assisted reproduction. However, the women in our study were relatively young, lean, and had a lower prevalence of HI and IR.…”
Section: Discussionmentioning
confidence: 66%
“…Combined extracts were dried in a SpeedVac and dissolved in 20 µL 5% formic acid. LC-MS/MS of the tryptic peptides was performed using the Ultimate 3000 HPLC system coupled online to a Q-Exactive-Plus mass spectrometer with a NanoFlex source (both from Thermo Fisher Scientific) equipped with a stainless-steel emitter as previously described (Nagy et al, 2019). For the database search and label-free quantitation (LFQ), the software PEAKS X (Bioinformatics Solutions Inc., Waterloo, Ontario, Canada) was applied to the spectra to search against the Human SwissProt database (20,404 entries).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…The FF harbors different hormones produced by the cells of the follicular microenvironment [ 5-8 ], as well as other molecules related to the redox homeostasis [ 9-12 ]. Although biomarkers of oxidative stress, hormones, and other molecules have already been evaluated in the FF [ 12 , 13 ], there is no consensus in the literature about their influence on the oocyte physiology [ 9 , 10 , 14 , 15 ]. This lack of consensus can be related to the criteria used for the admission of FF samples within these studies; the methodological differences in the measurement of analytes, patient age, body mass index (BMI), infertility or other disease diagnosis; human ability with ART procedure; or the psychophysiological characteristics of each woman (or couple).…”
mentioning
confidence: 99%